ChemInform Abstract: Practical Ni‐Catalyzed Aryl—Alkyl Cross‐Coupling of Secondary Redox‐Active Esters. Issue 33 (27th July 2016) - Cornella, Josep; Edwards, Jacob T.; Qin, Tian; Kawamura, Shuhei; Wang, Jie; Pan, Chung‐Mao; Gianatassio, Ryan; Schmidt, Michael; Eastgate, Martin D.; Baran, Phil S.
Abstract: Simple alkyl carboxylic acids are coupled with aryl zinc reagents under Ni‐catalysis.